The Aedes aegypti RNA interference response against Zika virus in the context of co-infection with dengue and chikungunya viruses. - Mayke Leggewie; Christina Scherer; Mine Altinli; Rommel J Gestuveo; Vattipally B Sreenu; Janina Fuss; Marie Vazeille; Laurence Mousson; Marlis Badusche; Alain Kohl; Anna-Bella Failloux; Esther Schnettler (PLoS Neglected Tropical Diseases)
Since its detection in 2015 in Brazil, Zika virus (ZIKV) has remained in the spotlight of international public health and research as an emerging arboviral pathogen. In addition to single infection, ZIKV may occur in co-infection with dengue (DENV) and chikungunya (CHIKV) viruses, with whom ZIKV shares geographic distribution and the mosquito Aedes aegypti as a vector. The main mosquito immune response against arboviruses is RNA interference (RNAi). It is unknown whether or not the dynamics of the RNAi response differ between single arboviral infections and co-infections. In this study, we investigated the interaction of ZIKV and DENV, as well as ZIKV and CHIKV co-infections with the RNAi response in Ae. aegypti. Using small RNA sequencing, we found that the efficiency of small RNA production against ZIKV -a hallmark of antiviral RNAi-was mostly similar when comparing single and co-infections with either DENV or CHIKV. Silencing of key antiviral RNAi proteins, showed no change in effect on ZIKV replication when the cell is co-infected with ZIKV and DENV or CHIKV. Interestingly, we observed a negative effect on ZIKV replication during CHIKV co-infection in the context of Ago2-knockout cells, though his effect was absent during DENV co-infection. Overall, this study provides evidence that ZIKV single or co-infections with CHIKV or DENV are equally controlled by RNAi responses. Thus, Ae. aegypti mosquitoes and derived cells support co-infections of ZIKV with either CHIKV or DENV to a similar level than single infections, as long as the RNAi response is functional.